Faster, higher, stronger… safer? Safety concerns for young athletes in Zambia. (September 2019) - Solstad, Gerd Marie; Strandbu, Åse
This article draws attention to safety concerns affecting young people in the setting of organized sport in Zambia. Our primary aim is to explore ways in which aspects of sport culture may constitute a threat to athlete safety. Secondly, we try to understand sport-specific safety concerns in light of more general concerns for young people's safety in Zambia. The study is based on interviews with athletes, coaches and sports leaders from Zambian sport. Although sport was mainly described as a positive recreational arena for youth, concerns were raised about unequal power relations and problematic ideals in the sport culture. Our findings suggest a need to discuss critically how glorification of toughness and resilience might contribute to normalize harmful practices in sport. Further, we indicate that divergent and elusive understandings of violence and abuse – in research and in practice – can influence athlete safety in significant ways. We conclude that safeguarding in sport continues to exist in the tension between protecting athletes from harm on the one hand and subscribing to a culture that promotes the ideals 'faster, higher, stronger' on the other.